2005
DOI: 10.1590/s1020-49892005001000002
|View full text |Cite
|
Sign up to set email alerts
|

Factores socioeconómicos y contextuales que determinan la actividad reproductiva de las adolescentes en Colombia

Abstract: Sex education has been provided in the schools in Colombia since 1993, but our results clearly indicate that it has had only a limited impact on the reproductive behavior of adolescent women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
34

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 6 publications
0
23
0
34
Order By: Relevance
“…The risks related to health, financial and emotional conditions, continuity of education and difficulties related to access to work were the main factors contributing to the increase of vulnerability in adolescent mothers (5)(6) .…”
Section: Latinmentioning
confidence: 99%
“…The risks related to health, financial and emotional conditions, continuity of education and difficulties related to access to work were the main factors contributing to the increase of vulnerability in adolescent mothers (5)(6) .…”
Section: Latinmentioning
confidence: 99%
“…Como sea, la familia constituye el pilar de la sociedad pues es el centro de aprendizaje e inculcación de valores que le permiten al individuo salir a enfrentar la sociedad de manera integral y responsable (17); por tanto, es primordial que sea funcional, que el adolescente perciba en ella la posibilidad de participación, confianza y soporte emocional. Como lo confirma esta investigación, prima la función sobre la estructura, siendo la disfunción familiar un importante factor relacionado con los comportamientos sexuales de riesgo en torno a la sexualidad.…”
Section: Discussionunclassified
“…Among these factors are macrosocial factors including (1) sociocultural norms, such as the increase in commonality of early sexual initiation, the need to have children to demonstrate femininity, low societal expectations for women, and the cultural perception that the basic role of women is reproduction and domestic work (Pantelides, 2004;Remez, 1989;Stern, 2004;Torres, 1998); (2) the characteristics of the neighborhood/community (Crane, 1991;Hogan and Kitagawa, 1985;Pantelides, 2004;Singh, Darroch, and Frost, 2001); and (3) public policies, particularly those related to the provision of health services, sexual education, and family planning (Flórez, 2005;Flórez and Núñez, 2001;Flórez et al, 2004;Pantelides, 2004). Other factors associated with adolescent fertility are exposure to the risk of pregnancy, such as age at first sexual intercourse, early marriage/union, knowledge and use of contraceptives, and availability/legality of abortion (Barrega and Higuera, 2004;Flórez, 2005;Flórez and Núñez, 2001;Flórez et al, 2004;Stern, 2004). Lastly, some authors have argued that there is social vulnerability to teenage pregnancies, meaning that adolescent pregnancy is more prevalent among the groups that are structurally or temporarily excluded (Singh, Darroch, and Frost, 2001;Stern, 2004).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Studies on the determinants of teenage pregnancy and motherhood on Latin American countries are more scant, and have focused on socioeconomic, cultural, and public policy factors, as well as exposure risks. Three recent studies using Colombian data suggest that contextual and socioeconomic factors-such as education, the teenager's marital status, family history of teenage fertility, and lack of parental supervision-are important determinants of teenage pregnancy and motherhood (Barrera and Higuera, 2004;Flórez, 2005;Flórez et al, 2004). A study on Mexican teenagers found that teenage pregnancy in Mexico is primarily a response to the social context of the adolescent, particularly her marital status, age, and educational level (Menkes and Suárez, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation